Preparation and Characterization of Curcumin-loaded Cellulose Nanoparticles - Chiu, Hock Ing (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Curcumin possesses diverse pharmacological activities such as anti-inflammatory, anti-carcinogenic and antioxidant but its uses are limited by its poor bioavailability and low water solubility. The objective of this study is to prepare curcumin loaded cellulose nanoparticles and to optimise the loading efficiency and loading capacity of curcumin in cellulose nanoparticles. Curcumin loaded cellulose nanoparticles with a mean size of 114 nm and size range of 73-263 nm in diameter were successfully regenerated by using in situ nanoprecipitation technique. Different parameters such as ratio of cellulose solution to ethanolic curcumin solution, concentration of ethanolic curcumin solution, concentration of surfactant (Tween 80), and loading durations were controlled to examine the loading efficiency and loading capacity of curcumin in cellulose nanoparticles. The UV-visible spectra showed a characteristic absorption peak at 470 nm. The functional groups of chemical structure, morphology, and mean size of curcumin-loaded nanoparticles were characterized by using FTIR, SEM and TEM. 2.38 mg/mg loading capacity and 30.57% loading efficiency of curcumin were obtained using 1:6 (v/v) phase ratio with 0.1 mg/mL ethanolic curcumin solution within 1 hour loading.